1997
DOI: 10.1016/s0005-2728(97)00053-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitroso compounds on Na/K-ATPase

Abstract: Thiol containing NO.-derivatives were found to inhibit the activity of brain and kidney Na/K-ATPase. S-Nitrosogluthatione demonstrated only minor inhibiting activity, while dinitrosyl iron complexes (DNIC) with cysteine or glutathione were much more effective. Brain Na/K-ATPase is more vulnerable to inhibiting action than kidney Na/K-ATPase. Inhibition of the activity is accompanied by a decrease in amount of protein thiol groups and a change in the substrate dependence curve of the enzyme. Restoration of Na/K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 24 publications
1
45
1
Order By: Relevance
“…25% inhibition) under the same conditions. A possible explanation for this discrepancy could be ascribed to the different isoforms present in porcine cerebral cortex (essentially α 2 + α 3 ) and rat erythrocyte (essentially α 1 ), even if Na + /K + -ATPase from brain has been reported to be more vulnerable to oxidative modification than that from kidney (Xie et al, 1995;Boldyrev et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…25% inhibition) under the same conditions. A possible explanation for this discrepancy could be ascribed to the different isoforms present in porcine cerebral cortex (essentially α 2 + α 3 ) and rat erythrocyte (essentially α 1 ), even if Na + /K + -ATPase from brain has been reported to be more vulnerable to oxidative modification than that from kidney (Xie et al, 1995;Boldyrev et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…15 N NMR spectra were recorded at 50.671 MHz, and 1024 transients were acquired with 2 s delay time. Chemical shifts (d) of 15 N NMR spectra are relative to neat 1 m NaNO 2 in D 2 O (d = 232 ppm) as the external standard. [31] Analyses of carbon, hydrogen, and nitrogen were obtained using a CHN analyzer (Heraeus).…”
Section: Methodsmentioning
confidence: 99%
“…(1-NAP) (yield 75 %) characterized by IR (ñ NO = 1808 (w), 1775 (s), 1751 cm À1 (s) (THF)), 15 N NMR, and UV/Vis spectroscopy, and singlecrystal X-ray diffraction. The single-crystal X-ray structure of 1-NAP is depicted in Figure S3 8 ]THF), which were assigned to anti (C 2h ) and syn configurations (C 2v ), respectively ( Figure S4 in the Supporting Information).…”
mentioning
confidence: 99%
“…These metabolites, for example, can cause genotoxic effects by creating DNA damage [86]. In some other studies, N-nitroso compounds have been reported to alter the activity of creatine kinase, lactate dehydrogenase [87], pyruvate kinase [88], and Na/K-ATPase [89] enzymes.…”
Section: Nos Isoforms In Carcinogenesismentioning
confidence: 99%